2003
DOI: 10.1530/rep.0.1250369
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in cumulus cells during in vitro maturation of bovine cumulus-enclosed oocytes

Abstract: The aim of this study was to investigate whether apoptosis occurs in cumulus cells during in vitro maturation (IVM) of bovine cumulus-enclosed oocytes (CEOs). The bovine CEOs obtained from ovaries from an abattoir were cultured for 24 h in IVM medium in the presence or absence of 10% (v/v) fetal bovine serum. The developmental competence of enclosed oocytes, as assessed by the development of the blastocyst after IVF, was significantly higher in the serum-treated group than in the control group. The morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 2 publications
6
45
0
Order By: Relevance
“…The ladder-like PCR products in CEOs were hardly detectable at 0 h of IVM, while they increased after 12 h of culture and toward the end of IVM (24 h), irrespective of MK addition. The sizes of the ladders observed were, as expected, 185 bp multiples with additional 24 bp oligonucleotides at each DNA end corresponding to the apoptotic internucleosomal fragments (Ikeda et al 2003). When compared at each time point, the apoptotic index was significantly lower in the MK-treatment group at 18 and 24 h of IVM than in the control.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The ladder-like PCR products in CEOs were hardly detectable at 0 h of IVM, while they increased after 12 h of culture and toward the end of IVM (24 h), irrespective of MK addition. The sizes of the ladders observed were, as expected, 185 bp multiples with additional 24 bp oligonucleotides at each DNA end corresponding to the apoptotic internucleosomal fragments (Ikeda et al 2003). When compared at each time point, the apoptotic index was significantly lower in the MK-treatment group at 18 and 24 h of IVM than in the control.…”
Section: Resultssupporting
confidence: 73%
“…We previously showed that apoptosis occurs in cumulus cells during IVM of CEOs (Ikeda et al 2003). We tentatively refer to this phenomenon as IVM-induced apoptosis because apoptosis is unlikely to occur in cumulus cells during natural (i.e.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations